A coupled and coordinated analysis in livelihoods of poverty alleviation migrants from a just transition perspective - Tao, Siji; Shi, Guoqing (Frontiers in Sustainable Food Systems, 2023)
Introduction From 2016 to 2020, China resettled 9.6 million poor people for the purpose of poverty alleviation. While this policy achieved the goal of eliminating absolute poverty, it also caused massive displacement and problems related to achieving a “just transition”. This study considers the “coupled coordination model” of resettlement, and examines livelihood capital and livelihood stability, from the perspective of “just transition”. Methods This study is based on survey data gathered in Lanping County, Yunnan Province from 235 resettled people that belong to “ethnic minority groups directly-entering-socialism”, making use of the livelihood capital assessment index system of farm households which is based on China's poverty alleviation resettlement policy and background-established a “coupled coordination degree model” which coordinates and combines livelihood capital and livelihood stability analyzes how accumulation of livelihood capital affects livelihood stability. Results Results indicate that (1) resettlement and supportive measures increased the coupling and coordination of migrants' household livelihood capital and livelihood stability.; (2) This type of coupled coordination led to a change from “dysfunctional decline type” to a “transitional development type”, thus reflecting “just transition”; (3) Although livelihood capital had an important positive impact on the coupling and coordination of migrants livelihood coupling and coordination, different livelihood strategies influenced livelihood coupling and coordination in different ways. Discussion This requires that government decision makers focus on facilitating a “just transition” as migrants become urbanized citizens. Disposing of natural resources such as farmland for migrants, promoting the implementation of land circulation policies, considering the contribution of different types of livelihood capital to different families, improving the precision of employment training, and promoting sustainable livelihood development.